2020
DOI: 10.1183/13993003.02105-2020
|View full text |Cite
|
Sign up to set email alerts
|

The (in)significance of TB and COVID-19 co-infection

Abstract: We read with great interest the research letter by TADOLINI et al. [1], in which they have published the first cohort of 49 cases of tuberculosis (TB) and coronavirus disease 20019 (COVID-19) co-infection. However, a few issues regarding the letter need to be addressed. The authors categorised the patients with TB and COVID-19 co-infection into 3 groups based on timing of their diagnosis. However, in view of the difference in the natural history of TB (chronic course) and COVID-19 (acute), categorising 14 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 6 publications
0
42
0
7
Order By: Relevance
“…The authors divided patients into cases with TB before COVID-19, those with COVID-19 followed by TB, and those in whom these two infections occurred in the same week. There was some discussion in the literature about the interpretation of the findings, particularly regarding the timing, with the suggestion that since TB has a chronic course, while COVID was an acute illness, this co-infection may be purely incidental; however, there was concern about the high mortality of that study of 12.3% in the cases with apparent co-infections, which is higher than that for COVID alone [ 74 , 75 ]. There was also a concern though, aside from these comments, that these co-infections, even if co-incidental, may nevertheless be an issue in countries with high TB (and post-TB sequelae) burdens and that both infections could have a significant, synergistic social and economic impact worldwide [ 74 ].…”
Section: Clinical Data On Co-infections With Covidmentioning
confidence: 99%
“…The authors divided patients into cases with TB before COVID-19, those with COVID-19 followed by TB, and those in whom these two infections occurred in the same week. There was some discussion in the literature about the interpretation of the findings, particularly regarding the timing, with the suggestion that since TB has a chronic course, while COVID was an acute illness, this co-infection may be purely incidental; however, there was concern about the high mortality of that study of 12.3% in the cases with apparent co-infections, which is higher than that for COVID alone [ 74 , 75 ]. There was also a concern though, aside from these comments, that these co-infections, even if co-incidental, may nevertheless be an issue in countries with high TB (and post-TB sequelae) burdens and that both infections could have a significant, synergistic social and economic impact worldwide [ 74 ].…”
Section: Clinical Data On Co-infections With Covidmentioning
confidence: 99%
“…[29][30][31] One clinical study suggests that comorbidity with TB manifests atypical radiological features in individuals diagnosed with COVID-19. 32 Although a clear causal relationship between the two is debated, 33 the similarities in their initial physiological symptoms and shared risk factors (including poverty, overcrowding, and air pollution) mean that M. tuberculosis and SARS-CoV-2 are two intertwined infectious agents whose coinfection likely leads to worse prognosis than either one alone. [29][30][31]33 Indirectly, the ongoing pandemic redirects resources and attention away from TB, as well as from HIV and malaria.…”
Section: Resultsmentioning
confidence: 99%
“…32 Although a clear causal relationship between the two is debated, 33 the similarities in their initial physiological symptoms and shared risk factors (including poverty, overcrowding, and air pollution) mean that M. tuberculosis and SARS-CoV-2 are two intertwined infectious agents whose coinfection likely leads to worse prognosis than either one alone. [29][30][31]33 Indirectly, the ongoing pandemic redirects resources and attention away from TB, as well as from HIV and malaria. Restrictions in international commerce that limit access to necessary medications, shifts in manufacturing of TB diagnostic tests to COVID-19 tests, and reallocation of financial and human resources towards COVID-19 are only a few of many concerns for the future of TB control.…”
Section: Resultsmentioning
confidence: 99%
“…The average proportion of MDR-TB cases with XDR-TB was 6.2%. Poor regimen selection, inadequate drug supply and poor adherence of patients to the 6-months therapy may lead to development of drug-resistant Mtb strains, including multidrug-resistant (MDR-TB: resistant at least to INH and RIF) and extensively-drug-resistant (XDR-TB) strains [9].MDR-TB and XDR-TB still being a challenge for clinicians and staff operating in national TB programs [10]Considering the high worldwide prevalence of TB and current increasing burden of COVID-19, recent study showed a mortality much higher than isolated COVID-19 in the patients with dual infection [11,12] In the African Region, where the burden of HIV-associated TB is highest, 87% of TB patients had a documented HIV test result. A total of 477 461 TB cases among HIV-positive people were reported, of which 86% were on antiretroviral therapy [1].…”
Section: Introductionmentioning
confidence: 99%